2014
DOI: 10.1136/annrheumdis-2013-205058
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and cardiovascular risk factors predict rapid progression of atherosclerosis in rheumatoid arthritis

Abstract: Objective To estimate atherosclerosis progression and identify influencing factors in rheumatoid arthritis (RA). Methods We used carotid ultrasound to measure intima-media thickness (IMT) in RA patients, and ascertained cardiovascular (CV) risk factors, inflammation markers and medications. A second ultrasound was performed approximately 3 years later. We calculated the progression rate by subtracting the baseline from the follow-up IMT, divided by the time between the two scans. We used logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 32 publications
(16 reference statements)
5
64
0
9
Order By: Relevance
“…In patients with RA, the excess cardiovascular disease risk appears to be comparable with that found in patients with type 2 diabetes mellitus 6, 7. Both conventional cardiovascular risk factors (eg, hypertension, obesity, dyslipidemia, and diabetes mellitus) and increased systemic inflammation play a contributory role 4, 8, 9…”
Section: Introductionmentioning
confidence: 82%
“…In patients with RA, the excess cardiovascular disease risk appears to be comparable with that found in patients with type 2 diabetes mellitus 6, 7. Both conventional cardiovascular risk factors (eg, hypertension, obesity, dyslipidemia, and diabetes mellitus) and increased systemic inflammation play a contributory role 4, 8, 9…”
Section: Introductionmentioning
confidence: 82%
“…Studies on IMT in RA patients also demonstrated that systemic inflammation and CV risk factors were associated with rapid IMT progression. MTX and anti-TNFα agents may influence IMT progression by reducing the effect of the systemic inflammation on the IMT [41]. Creactive protein (CRP) and erythrocyte sedimentation rate (ESR) were similarly associated with higher risk of myocardial infarction as well as stroke, reflecting the prominent role of inflammation in CHD risk in RA [42].…”
Section: Inflammatory Markersmentioning
confidence: 96%
“…Interestingly, CPP have been found in the blood of patients with CKD and in the dialysate obtained from patients receiving peritoneal dialysis [6,16,36]. CPP have also been detected in the blood of patients with inflammatory rheumatoid diseases but normal renal function, a population at increased risk for the development of atherosclerosis [3,9].…”
Section: Introductionmentioning
confidence: 97%